Parents' willingness to pay for the prevention of childhood overweight and obesity - Kesztyüs, Dorothea (Health Econ Rev, 2014)
OBJECTIVE: To determine parental willingness-to-pay (WTP) for childhood obesity prevention. METHODS: Cross-sectional data from the follow-up measurements (2011) of a health promotion programme in German primary schools. Data collection included anthropometric measurements of children and self-administered questionnaires for parents, including WTP assessment. Mann-Whitney U-Test was used for differences between groups, and regression analysis to identify factors associated with general WTP and amount of WTP. RESULTS: From 1 534 parents, 97.8% considered overweight/obesity to be serious public health problems. A general WTP to reduce the incidence of childhood overweight/obesity by half, was declared by 48.8%. Parents of overweight/obese children showed with 61.4%, significantly more frequently, their general WTP than the others with 47.2% (p = 0.001). Mean WTP was €23.04 (99% confidence interval (CI) [22.45; 23.75]) per month. Parents of centrally obese children showed significantly higher WTP than parents of the other children (p = 0.001). General WTP and the amount of WTP were associated with the central obesity of the child, migration status and household income. Additionally, general WTP was associated with maternal obesity. CONCLUSIONS: Nearly half of the parents were willing to invest in prevention of obesity. The general WTP significantly occurs more often and with higher amount in affected parents. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13561-014-0020-8) contains supplementary material, which is available to authorized users.